2020
DOI: 10.1016/j.omtn.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PVT1 Promotes Tumorigenesis of Colorectal Cancer by Stabilizing miR-16-5p and Interacting with the VEGFA/VEGFR1/AKT Axis

Abstract: Recently, the long noncoding RNA (lncRNA) plasmacytoma variant translocation 1 (PVT1) was reported to be involved in the pathogenesis of several cancers, including human colorectal cancer (CRC). However, the molecular basis for cancer initiation, development, and progression remains unclear. In this study, we observe that upregulated PVT1 is associated with poor prognosis and bad clinicopathological features of CRC patients. In vitro means of PVT1 loss in a CRC cell line inhibit cell proliferation, migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…Its aberrant expression can be a relatively independent regulatory factor for promoting tumorigenesis and MYC [ 22 , 23 , 24 ]. The upregulation of PVT1 suggests that it can be used for the early detection of cancer, the prognostication of drug resistance, or as a therapeutic target [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its aberrant expression can be a relatively independent regulatory factor for promoting tumorigenesis and MYC [ 22 , 23 , 24 ]. The upregulation of PVT1 suggests that it can be used for the early detection of cancer, the prognostication of drug resistance, or as a therapeutic target [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…PVT1 is known to regulate functions of microRNAs (miRNA) during tumorigenesis [31,32]. We identi ed a region in miR-21-5p having a complementary binding sequence to PVT1, using Starbase 3.0 [33], and also generated a binding-de cient mutant of PVT1 (PVT1-mut) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Altered lncRNA expression patterns for microsatellite-stable colorectal cancer indicated that several lncRNAs were continuously upregulated/downregulated during the adenoma-adenocarcinoma sequence [29] . Unlike previous studies that focused on one or more lncRNAs in CRC [30][31][32] , we rst conducted a systematic and comprehensive analysis using microarrays to reveal the differentially expressed pro les of lncRNAs and mRNAs in the malignant evolutionary process for pMMR CC. Thousands of dysregulated transcripts were identi ed in the ACS, including 5783 lncRNAs and 4483 mRNAs.…”
Section: Discussionmentioning
confidence: 99%